Exploring maternal identity formation of first time mothers who gave birth through a non-elective caesarean section - Lazarus, Kim Yael (My University, 2017)
The performance of Caesarean sections is increasing around the world. In recent years, South Africa has seen a substantial rise in the number of Caesarean section deliveries. Literature has focused on the incorporation of the maternal role into a women’s identity post-partum in general. However, less emphasis has been placed on how an unplanned method of delivery such as a non-elective Caesarean section influences this process against a backdrop of societal and self-imposed expectations. The current study explored the process of maternal identity formation of first time mothers who delivered their babies through a non-elective Caesarean section. The sample consisted of six first time mothers who gave birth through a non-elective Caesarean section. This is a qualitative, Interpretative Phenomenological Analysis (IPA) research design that utilized semistructured interviews. The data was analyzed with the use of thematic analysis. Findings indicated that there is a strong need for mothers to be seen as ‘good enough’ and this impacts their ability to process their own birthing experience. There seems to exist negative judgment by other mothers and society in general around delivering through a Caesarean section; however the nature of this stigma cannot be named due to its impact on maternal identity. Other important themes that emerged include flexibility and control, the importance of support, and the psychological role of labor as a means of preparation for processing the idea of giving birth through a non-elective Caesarean section.
This is a research project submitted in partial fulfillment of the requirements for the degree of Masters in Clinical Psychology in the department of Psychology, University of the Witwatersrand, Johannesburg, 8 December 2016.
Keywords: Cesarean section--Social aspects; Cesarean section--Complications